High-performance multi-scale control scheme for stable, integrating and unstable time-delay processes - Nandong, Jobrun; Zang, Zhuquan (Elsevier Science Ltd., 2013)
This paper presents a new multi-scale control scheme which is applicable to both stable and integrating/unstable time-delay processes. The salient feature of the proposed scheme is to decompose a given plant into a sum of basic modes, where an individual sub-controller is specifically designed to control each of these modes. An overall multi-scale controller is then synthesized by combining all the sub-controllers in such a way to achieve good cooperation among the different plant modes as to achieve good nominal performance and performance robustness. Extensive numerical study shows that the proposed multi-scale control scheme provides substantial improvement in control performance/robustness over the classical Smith predictor and some of its well-established variants.